Coexistence between primary and secondary cavity-nesting birds in Chelia-Ouled Yagoub National Park of Algeria - Badis, Mehdi; Benchana , Imane; Hamdi , Nabil (Algerian Journal of Biosciences, 2023)
In forest ecosystems, the cavity-nesting community is strongly dependent on the availability of tree cavities in which the breeding season takes place. This work aims to investigate links between two ecological groups as primary and secondary cavity-nesting species. The investigations carried out using the count point method, during two breeding seasons from Mars to July 2018 and 2019, made it possible to distinguish eight species of cavity-nesting birds; only the Levaillant’s Woodpecker Picus vaillantii constitutes a primary cavity able to dig its cavities. In the Chelia-Ouled Yagoub National Park, the modeling of the occurrence data highlights a significant coexistence between the latest species and only three secondary cavity-nesting species, namely the Atlas Pied Flycatcher Ficedula speculigera, the Eurasian Hoopoe Upupa epops, and the Short-toed Treecreeper Certhia brachydactyla. This result supports the consideration of woodpeckers as keystone species for biodiversity, whose protection leads to the conservation of forest balance in general.